Is there any link among sibutramine, ghrelin and cholesterol? - Aydin, Suna; Aydin, Suleyman (Turkish Biochem Soc, 2010)
[Abstract Not Available]
Sibutramin, ghrelin, ve kole sterol arasında bir ba?lantı olabilir mi?